The Anti-Union (JSTOR)
The Anti-Union was a short lived publication at the end of the eighteenth century. It lasted less than three months and consisted of only thirty-two numbers. Conceived in the aftermath of the 1798 rebellion (May?Sep.), this political periodical explored the issues surrounding an incorporated union with Britain. The Anti-Union opposed the impending union between Ireland and Britain which was being proposed in the political sphere at this time.
Keywords: Irish Studies